The effectiveness of the games based learning model in improving students' lower passing skills - Yungmi Muliadi; Muhamad Sazeli Rifki; Eval Edmizal; Sepriadi Sepriadi (Journal of Educational and Learning Studies, 2026)
This study aimed to examine the effectiveness of the Games Based Learning (GBL) model in improving volleyball lower passing skills among Grade X students at SMKN 1 Solok Selatan. A quantitative quasi-experimental study employing a Non-equivalent Control Group Pretest–Posttest Design was conducted. The sample consisted of 69 students selected through total sampling, including 35 students in the experimental group and 34 students in the control group. The experimental group received Games Based Learning instruction, while the control group received conventional instruction. Data were collected using a lower passing skills test assessing passing accuracy, strength control, and movement consistency. Data were analyzed using N-Gain analysis, Paired Sample t-tests, and Independent Sample t-tests. The experimental group showed a significant improvement (t = −13.834, p < 0.001) with an N-Gain of 0.5191 (moderate), whereas the control group achieved an N-Gain of 0.2922 (low). A significant difference was found between groups (t = 3.503, p < 0.001). Games Based Learning was more effective than conventional instruction in improving students’ volleyball lower passing skills and is recommended for physical education learning.